Palladium-catalyzed aerobic dehydrogenative aromatization of cyclohexanone imines to arylamines - Hajra, Alakananda (2013)
Dehydrogenative aromatization of cyclohexanone imines to arylamines has been achieved using a palladium catalyst under aerobic conditions. The reaction is applicable to a variety of imines that are either preformed or generated in situ from cyclohexanone derivatives and aryl or alkylamines.